Struktur Komunitas Larva Ikan Pada Ekosistem Padang Lamun Di Perairan Jepara - Ita Riniatsih (Universitas Diponegoro, 2016)
Seagrass meadow ecosystem as one of the ecosystems in the coastal region that is productive has an ecological function as a place for spawning, care for larvae produced and a place to find various marine organisms that live in it. The sustainability and diversity of marine organisms is very dependent on the biophysical presence and condition of seagrass beds as a temporary habitat or habitat during its life cycle. Research on the study of the ecological functions of seagrass beds was carried out to see how far the connection between seagrass meadows conditions and fish larvae diversity used seagrass meadows for shelter and foraging. This descriptive method research was carried out in the Jepara seagrass ecosystem in Teluk Awur, Bandengan Beach and Mororejo waters. Fish samples are caught using a blade, which is pushed 150 meters along the coastline. The total number of fish larvae caught during the study was 570 from 12 families. The identification results showed that the fish families caught were Apogonidae, Carapidae, Blenniidae, Egraulidae, Epilephenidae, Gerridae, Heniranphidae, Labridae, Gobiidae, Lutjanidae, Syngnathidae, Mullidae, and Siganidae. Fish families identified were dominated by Gobiidae, Bleniidae and Eugraulidae families. Based on the location of observation, the Bandengan waters location is the location with the highest fish larvae catches, as many as 9 families, as many as 7 families of Teluk Awur waters and Mororejo waters as many as 5 families. Ekosistem padang lamun sebagai salah satu ekosistem di wilayah pesisir yang produktif mempuyai fungsi secara ekologis sebagai tempat untuk memijah, daerah asuhan bagi larva yang dihasilkan dan tempat untuk mencari makan berbagai organism laut yang hidup di dalamnya. Kelestarian dan keanekaragaman organism laut sangat tergantung dari keberadaan dan kondisi biofisik padang lamun sebagai habitat sementara atau habitat selama siklus hidupnya. Penelitian tentang kajian fungsi ekologis padang lamun ini dilakukan untuk melihat seberapa jauh keterkaitan tentang kondisi padang lamun dengan keaneragaman larva ikan yang memanfaatkan padang lamun untuk tempat berlindung dan mencari makan. Penelitian dengan metoda deskriptif ini dilakukan di ekosistem padang lamun Jepara di perairan Teluk Awur, Pantai Bandengan dan perairan Mororejo. Sampel ikan di tangkap dengan menggunakan jarring sudu, yang didorong sepanjang 150 meter sejajar garis pantai. Jumlah total larva ikan yang tertangkap selama penelitian adalah sebanyak 570 ekor dari 12 famili. Hasil identifikasi memperlihatkan famili ikan yang tertangkap adalah Apogonidae, Carapidae, Blenniidae, Egraulidae, Epilephenidae, Gerridae, Heniranphidae, Labridae, Gobiidae, Lutjanidae, Syngnathidae, Mullidae, dan Siganidae. Famili ikan yang teridentifikasi didominasi dari famili Gobiidae, Bleniidae dan Eugraulidae. Berdasarkan lokasi pengamatan, lokasi perairan Bandengan merupakan lokasi dengan hasil tangkapan larva ikan tertinggi, yaitu sebanyak 9 famili, perairan Teluk Awur sebanyak 7 famili dan perairan Mororejo sebanyak 5 famili.